FAMILY PLANNING AWARENESS AND UTILIZATION INTENTIONS AMONG WOMEN USING ANTENATAL CARE SERVICES IN KADUNA METROPOLIS - Sani, Jamilu; Yusuf, R. O.; Arigbede, Y. A. (FUDMA JOURNAL OF SCIENCES, 2023)
Awareness on family planning (FP) among women stimulates acceptance and intention to use which gives the opportunity of choice in their reproductive activities. This study examines these relationships in Kaduna metropolis among women attending antenatal care (ANC) services. The study used multi-stage sampling technique to administer research instrument to the 386 respondents. Data were analysed using descriptive and Chi-Square. The results show that about 90% of women in the study were aware of FP and majority know it through health workers in hospitals. About 59% of the respondents reported to have previously used FP while 74% still had the intention to use FP in the future. Pills and implant are the major methods used with 29% and 21% respectively. There is a significant relationship between awareness on FP and intention to use (p= < .01). The study concluded that as awareness of FP increase, more women will continue to use FP services. It is thus recommended that FP awareness campaign should be intensified.
Keywords: family planning; antenatal care; utilization intention